Land use change and baseflow recession modelling in Wuryantoro Watershed, Wonogiri Regency, Central Java Province, Indonesia - Bokiraiya Latuamury; Mersiana Sahureka; Wilma Nancy Imlabla; Miranda H Hadijah; John F Sahusilawane; Husain Marasabessy; Moda Talaohu (Brawijaya University, 2022)
Hydrological phenomena on the scale of a watershed are complex and may never be understood holistically. One of the innovations in baseflow hydrological modelling is the analysis of the baseflow recession curve, generally expressed as the natural storage of river flows and containing valuable information about the properties and characteristics of natural aquifer storage. This study aims to model land use change and baseflow recession in the Wuryantoro watershed, Wonogiri Regency, Central Java Province. The research method uses an exponential model in which changes in the characteristics of a baseflow recession are a function of land use changes over a certain period. The calibration of the seven graphical models of land use change against the characteristics of the baseflow recession shows that the seven curves of the land use change graphic model have model coefficients and curve slopes that vary from gentle to steep. The slope of the gentle and steep curve describes the bottom flow deposits' condition over time. The state of water storage in the seven better graphical models is that the change of forest remains forest followed by the change of agriculture into the forest, forest into the settlement, change of agricultural land into the settlement, change of forest to agricultural land, settlement remains settlement and change of agricultural land remains agrarian land.